Dengue-Herpes Zoster Coinfection:A Case Report (Journal of Medicine, 2025)
Tropical mosquito-borne infections, such as dengue, pose a significant morbidity and mortality risks to human. Coinfection in dengue patients may be seldom reported, but it carries essential implications in patient management. Our case is a 16-year-old girl who presented with vesicular eruptions on her face along with a short duration of high-grade fever and aches. Despite the typical distribution of rashes associated with herpes zoster infection, given the endemicity and recent outbreak of dengue, her blood sample was tested for dengue, which came back positive.J MEDICINE 2025; 26(2): 160-162